2018
DOI: 10.1126/scisignal.aal4289
|View full text |Cite
|
Sign up to set email alerts
|

Extension of chemotactic pseudopods by nonadherent human neutrophils does not require or cause calcium bursts

Abstract: Global bursts in free intracellular calcium (Ca) are among the most conspicuous signaling events in immune cells. To test the common view that Ca bursts mediate rearrangement of the actin cytoskeleton in response to the activation of G protein-coupled receptors, we combined single-cell manipulation with fluorescence imaging and monitored the Ca concentration in individual human neutrophils during complement-mediated chemotaxis. By decoupling purely chemotactic pseudopod formation from cell-substrate adhesion, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 79 publications
(141 reference statements)
0
12
0
Order By: Relevance
“…Some studies have found no evidence for calcium gradients in neutrophils during chemotaxis 44 , 52 , though others have obtained evidence that leading-edge calcium signals play a critical role in chemotaxis of many different cell types 53 , 54 . In the present work, we observed leading-edge calcium signals in all motile neutrophils in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found no evidence for calcium gradients in neutrophils during chemotaxis 44 , 52 , though others have obtained evidence that leading-edge calcium signals play a critical role in chemotaxis of many different cell types 53 , 54 . In the present work, we observed leading-edge calcium signals in all motile neutrophils in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found no evidence for calcium gradients in neutrophils during chemotaxis 38,46 , though others have obtained evidence that leading-edge calcium signals play a critical role in chemotaxis of many different cell types 47,48 . In the present work, we observed leading-edge calcium signals in all motile neutrophils in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The intracellular signalling molecules PI3K and Rac, which have been proposed as drivers of chemotaxis, do not appear to play a direct role in chemotaxis, but instead fine-tune motility to all chemoattractants by regulating a step common to all chemoattractants, for example refilling of the intracellular calcium stores, and thus modulate the amplitude of the leading-edge calcium pulses. Some studies have found no evidence for calcium gradients in neutrophils during chemotaxis 38,46 , though others have obtained evidence that leading-edge calcium signals play a critical role in chemotaxis of many different cell types 47,48 . In the present work, we observed leading-edge calcium signals in all motile neutrophils in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte spreading on β 2 -integrin adhesion has also been shown to depend on µ-calpain activity [33,34]. By close observation of neutrophil pseudopod extension around a particle for phagocytosis, the timing of the Ca 2+ signal is seen to proceed immediately before the acceleration phase of engulfment, [28,35,36] and the link between Ca 2+ and acceleration is broken by inhibition of µ-calpain activity [28]. In µ-calpain null mice, neutrophils also fail to spread effectively and are aberrant in transendothelial migration [37].…”
Section: Signalling the Release Of Cell Surface Microridges/wrinklesmentioning
confidence: 99%